Land Rental Markets in the Process of Rural Structural Transformation : Productivity and Equity Impacts in China - Deininger, Klaus; Jin, Songqing (World Bank, Washington, DC, 2012)
The importance of land rental for overall economic development has long been recognized in theory, yet empirical evidence on the productivity and equity impacts of such markets and the extent to which they realize their potential has been scant. Representative data from China's nine most important agricultural provinces illustrate the impact of rental markets on households' economic strategies and welfare, and the productivity of land use at the plot level. Although there are positive impacts in each of these dimensions, transaction costs constrain participation by many producers, thus preventing rental markets from attaining their full potential. The paper identifies factors that increase transaction costs and provides a rough estimate of the productivity and equity impacts of removing them.